ショウワキチ ノ コウスイ ノ トクチョウ ト ソノ キセツ ヘンカ - 小西, 啓之; コニシ, ヒロユキ; 遠藤, 辰雄; エンドウ, タツオ; Konishi, Hiroyuki; Endoh, Tatsuo (1997)
P(論文) 南極昭和基地で行ったレーダーやマイクロ波放射計を使った1989年の総合的な「雲と降水」の観測を基に, 昭和基地付近の降水量及び降水をもたらす雲について解析し, 降水量, 降水をもたらす低気圧に伴う雲の構造, 降水の季節変化の特徴について調べた。1) レーダーの連続観測から, 1989年の昭和基地の年降水量は204mmと推定した。夏を除く季節に降水があり, 秋, 冬, 春に降水量の大きな差は現れなかった。2) 昭和基地付近の降水に大きく寄与する雲は, 南極沿岸部で最盛期を迎える温帯低気圧に伴う渦状の雲であることがわかった。この渦状の雲の外側は, 南極沿岸を西向きに周回する低温かつ水蒸気の少ない気団の上に低緯度側からの暖気が入り, 温暖前線状の層状の構造を持つことが分かった。また, その内側は良く発達した渦に一回りした寒気が入り込み, 寒冷前線性の対流性の雲を形成していた。3) 雲や低気圧の季節変化から, 秋は数多く沿岸に近づく低気圧によって降水がもたらされるのに対し, 春は数少ない低気圧から降水がもたらされていることがわかった。低気圧に伴う雲は春, 秋に多く, また, 沿岸部で発達する雲水量の多い背の高い雲は秋に多いことから, 南極沿岸に降水の寄与が大きい季節は秋であると考えられる。降雪の頻度が多い秋に比べ降雪の頻度が少ない春の降雪の有無がその年の降雪量の特徴を決めていると推定された。 Long-term observations of precipitating clouds were carried out by a vertical pointing radar, PPI radar and a 37 GHz microwave radiometer at Syowa Station (69°00′S, 39°35′E), Antarctica in 1989. It is concluded from the observations that precipitation near Syowa Station, Antarctica is mainly brought by cloud vortices associated with extratropical cyclones which advance to high latitude while developing to a mature stage. The seasonal variations of clouds and precipitation were analyzed corresponding to the seasonal changes of air temperature and sea ice area. The occurrence frequencies of cloud vortices which brought snowfall to Syowa Station increased in the fall and spring seasons corresponding to activity of the circumpolar trough. However, the activities of cloud systems that bring precipitation weaken in spring when the sea ice area expands to low latitudes, because of less supply of heat and vapor. In 1989,the amount of precipitation in spring brought by a few snowfall events was as large as the amount of precipitation in fall brought by frequent snowfall events. Radar observations revealed that there were three abundant snowfall seasons at Syowa Station and the amount of snowfall was uniform in all seasons except summer. The amounts of precipitation in fall, winter and spring were 74,74 and 53mm respectively. departmental bulletin paper